Gardening with free-range chickens for dummies - Manion, Bonnie Jo. (Laura Ann); Ludlow, Rob. 1955- 1906-1998. 1933- 1960- (Susan Maxine); 1952- 1949- 1954-; 1923- (Melvin Lawrence) (Hoboken, NJ John Wiley and Sons, 2013)
Provides guidance and step-by-step instructions for designing and implementing a host of different chicken-friendly garden plans, offers an overview of caring for a flock, and discusses the anatomy of a coop -- |c Source other than Library of Congress.
Creating Enough Shade.
Keywords: Chickens; Chickens -- Housing; Gardening to attract birds; Agriculture